(untitled) (Homiletic, 2014)
Although narrative preaching as a movement may have gone out of fashion in North American homiletics more than two decades ago, there has since been a resurgence of interest in the rhetorical function of biblical narratives along with the continuing exploration of more democratic, dialogical and open-ended homiletical forms. This study, therefore, suggests that the discipline of narratology can potentially combine these two elements by replicating the dynamics of biblical narratives in a variety of narrative sermon formats. By providing an examination of the elements of narratology, this approach seeks to reunite the often-separated elements of textual and homiletical form and function. The use of these narratological exegetical tools can then allow biblical narratives to assert a greater influence upon the form of the sermon itself, create an experience of the text for the listeners, and enable them to enter into the “world of words” of biblical narratives.